Sorafenib plus drug-eluting bead transarterial chemoembolization for early intrahepatic stage-progressed advanced hepatocellular carcinoma refractory to conventional transarterial chemoembolization - Fan, Wenzhe; Zhu, Bowen; Zheng, Xinlin; Yue, Shufan; Lu, Mingjian; Fan, Huishuang; Qiao, Liangliang; Li, Fuliang; Yuan, Guosheng; Wu, Yanqin; Zou, Xinhua; Wang, Hongyu; et al. (Journal of cancer research and clinical oncology, 2023)
Purpose To investigate the effectiveness and safety of the combination of sorafenib and drug-eluting bead transarterial chemoembolization (DEB-TACE) in the treatment of early intrahepatic stage-progressed advanced hepatocellular carcinoma (ISPA-HCC). Methods This study was approved by the ethics committees of six tertiary medical centers in China. Between October 2017 and October 2020, 213 patients with advanced HCC received either sorafenib combined with on-demand DEB-TACE (DTS group, n = 103) or sorafenib monotherapy (S group, n = 110). Overall survival (OS), time to progression (TTP), local tumor response, and adverse events (AEs) were compared between the two groups. Results The incidences of nause/vomiting, abdonimal pain, hyperbilirubinemia, fever and ALT/AST increasing were higher in the DTS group. The post-treatment partial response, objective response, and disease control rates were significantly higher in the DTS group than in the S group (51.5% vs. 23.6%; 56.3% vs. 25.5%; 77.7% vs. 56.4%, respectively). The median OS was significantly longer in the DTS group than in the S group [16.3 vs. 10.0 months; hazard ratio (HR) = 0.43; P < 0.001], as was the TTP (6.7 vs. 4.3 months; HR = 0.60; P = 0.001). In the DTS group, patients who received ≥ 2 sessions of DEB-TACE benefited more than those who received two sessions of DEB-TACE. Multivariate analysis revealed that the α-fetoprotein level and treatment allocation were independent predictors of OS and TTP. Conclusion The combination of sorafenib and DEB-TACE is safe and effective for the treatment of early ISPA-HCC.